Tracking football player movement from a single moving camera using particle filters - Dearden,A; Demiris,Y; Grau,O (IET, 2006)
This paper deals with the problem of tracking football players in a football match using data from a single moving camera. Tracking footballers from a single video source is difficult: not only do the football players occlude each other, but they frequently enter and leave the camera's field of view, making initialisation and destruction of a player's tracking a difficult task. The system presented here uses particle filters to track players. The multiple state estimates used by a particle filter provide an elegant method for maintaining tracking of players following an occlusion. Automated tracking can be achieved by creating and stopping particle filters depending on the input player data.